Assistance in Managing Content for the Culinary Park Website to Increase Visits in Katekan Gantiwarno Village, Klaten, Central Jawa - Nurkhamid, Nurkhamid; Munir, Agus Qomaruddin; Wardani, Ratna; Setiyawan, Ramadhana; Mustofa, Zaenal (Universitas Serang Raya, 2025)
Katekan Village Culinary Park, Gantiwarno, Klaten, Central Java, is a culinary tourism spot that was just inaugurated in July 2023 by the Regent of Klaten which aims to develop local MSME activities in the Klaten area of Central Java. Several problems include the need to open insights for culinary MSME actors to participate in developing culinary tourism spots, limited infrastructure, information systems, management, marketing and promotion, product quality and sustainability, and local community participation. The urgency lies in the potential to transform Katekan Village into an attractive tourism destination and provide better business opportunities for surrounding MSMEs. The method used in this PKM activity is Participation Action Research, involving the village government in managing information media and fostering information media management skills through websites, which impacts the increase in the number of visits. The output of this activity is an activity in the form of developing culinary park tourism in Katekan Village, Gantiwarno, Klaten, Central Java, with information technology media in the form of a prototype of a website-based culinary park information system which has an impact on increasing the number of visits by 70%.